Method of modifying physical properties of palm-based diacylglycerol oil - Tan, Chin Ping; Ng, Siou Pei; Lai, Oi Ming; Linm, Hong Kwong (2013)
The present invention discloses a method to modify the physical properties of palm-based diacylglycerol oil. Accordingly, the method, which provides a palm-based diacylglycerol oil composition having improved physical properties of pourability, flow behavior, texture and thermal behavior, comprises pre-heating palm-based diacylglycerol oil at 60?C to 140?C, adding an emulsifier and/or crystallization inhibitor into the pre-heated palm-based diacylglycerol oil, agitating the mixture of step until formation of a homogenous oil composition, and cooling the homogenous mixture.